PENGARUH PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG DAN TOTAL HUTANG TERHADAP LABA BERSIH - Astuti, Diani Windi; Satiman (CV. ALIM'SPUBLISHING, 2024)
Abstract. This research aims to empirically test and prove the influence of inventory turnover, accounts receivable turnover and total debt on net profit in primary consumer goods companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2022 period. Data collection was carried out via the website www.idx.co.id. The sampling technique for this research uses a purposive sampling technique. The total sample obtained was 30 companies, so that 180 observation data were obtained. The type of data in this research is secondary data obtained in financial reports using quantitative research methods. The analytical method used in this research is multiple linear regression. This research was processed using Eviews 9 Software. The results of this research show that simultaneously the variables Inventory Turnover, Receivables Turnover and Total Payables have a significant effect on Net Profit. The partial research results show that the Receivables Turnover variable has no effect on Net Profit mean while Inventory Turnover and Total Debts has an effect on Net Profit.